Relationship Between Life-Space Mobility and Health Characteristics in Older Adults Using Global Positioning System Watches. (April 2022) - Chung, Jane; Boyle, Joseph; Wheeler, David C.
This study aimed to examine the feasibility of using global positioning system (GPS) watches to examine relationships between GPS-based life-space mobility (LSM) metrics and self-report LSM and health measures (physical, psychological, and cognitive function) among older adults. Thirty participants wore a Fitbit Surge for 3 days. Eight spatial and temporal LSM measures were derived from GPS data. About 90% of in-home movement speeds were zero, indicating the sedentary lifestyle, but they made some active out-of-home trips as the total distance traveled and size of movement area indicated. There was a significant difference in total distance traveled and 95th percentile of movement speed between mild cognitive and intact cognition groups. GPS-based higher proportion of out-of-home time was significantly associated with greater functional fitness. Greater GPS use hours were significantly associated with higher cognition. These findings suggest the potential of GPS watches to continuously monitor changes in functional health to inform prevention efforts.